If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2 = -3 + 4x Reorder the terms: 2 + 9x = -3 + 4x Solving 2 + 9x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 9x + -4x = -3 + 4x + -4x Combine like terms: 9x + -4x = 5x 2 + 5x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + 5x = -3 + 0 2 + 5x = -3 Add '-2' to each side of the equation. 2 + -2 + 5x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = -3 + -2 5x = -3 + -2 Combine like terms: -3 + -2 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| 15w^2+31w-28=0 | | 0.05x-0.03y=9 | | 6b=52 | | 7m-25=24 | | 11n+5=137 | | 51-6x=21 | | p/2=6 | | -2x-5y=20 | | 14x+6=2(5x+3) | | 2.5x+48.9=15.0-8.8x | | 2(5x-2)-x=40 | | 17x-12y=-36 | | 3xy/9x | | (m-1)x^2-2(m+1)x+m+4=0 | | 2x+1y=-10 | | -6=5-11n | | a^2+9a-9fora=-9 | | -5X+2Y=-40 | | x+2x+6x+2=29 | | (9x-4)-x=68 | | 2.2(2q+1)= | | e+10=30 | | 2x^2-12-14=0 | | -5X+2Y=-20 | | (x^2)(x^3-27i)=0 | | 60r-50=16r-6 | | -4(-3)(1)(-2)(-6)= | | -7X+5Y=140 | | (x*x*x*x*x)+9*(x*x)=0 | | -2x+5y=-30 | | 12+12a=72 | | 3(x+4)-11=28 |